The Legal Politics Against Artificial Intelligence Crimes in Criminal Law Reform - Hidayatuzzakia, Hana; Widyawati, Anis; Martitah, Martitah (Jurnal Daulat Hukum, 2024)
Technological sophistication in adulthood has had a significant imact on social life. Artificial Intelligence acts and behaves like humans in the same aspects of speed and accuracy. The interpretation of AI when a criminal act is present can only be seen as a legal object. The purpose of this research is to find out and analyze the rules of Artificial Intelligence crimes in Indonesian positive law and to find out and analyze Artificial Intelligence policies in several other countries. This research uses a normative legal research method, namely an approach carried out by examining literature studies, international news, and the approach of the Law. The legislation used is Law No. 1 of 2024, the second amendment to Law No. 11 of 2008 concerning Information and Electronic Transactions. The results of the research show that the rules of AI Crime are still regulated in the Law on Information and Electronic Transactions concerning electronic systems and electronic agents. There is no specific policy in response to the problem of Artificial Intelligence. Foreign countries such as China, America, Europe have special regulations regarding the concept of AI. The state's obligation to protect and follow the dynamics of technology needs to be supported by legal certainty. Special regulations need to be presented as a form of the government's seriousness in carrying out legal reform.